2013
DOI: 10.1177/0748233713475524
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin prevents benzo(a)pyrene-induced toxicity in Wistar rats by modulating xenobiotic-metabolizing enzymes

Abstract: quinone oxidoreductase 1, sulfotransferases), cellular antioxidant enzyme heme oxygenase and total glutathione. The results reveal that silymarin possesses substantial protective effect against B(a)P-induced damages by inhibiting phase I detoxification enzyme CYP1A1 and modulating phase II conjugating enzymes, which were confirmed by histopathological analysis. Overall, the inhibition of CYP1A1 and the modulation of phase II enzymes may provide, in part, the molecular basis for the effect of silymarin against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 84 publications
(86 reference statements)
3
19
0
Order By: Relevance
“…Silymarin, a natural compound derived from milk thistle (Silybum marianum) is widely used in health supplements, medicines, and medical supplies related to liver disease and cancer, and has no reported side-effects [50][51][52]. Previous studies on silymarin focused on its role as an anti-oxidant and its anti-inflammatory properties against B[a]P-induced ROS formation via modulating detoxifying enzymes in vivo [28]. However, B[a]P-induced genotoxicity is mainly caused by damage from BPDE-DNA adducts as well as ROS-based DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silymarin, a natural compound derived from milk thistle (Silybum marianum) is widely used in health supplements, medicines, and medical supplies related to liver disease and cancer, and has no reported side-effects [50][51][52]. Previous studies on silymarin focused on its role as an anti-oxidant and its anti-inflammatory properties against B[a]P-induced ROS formation via modulating detoxifying enzymes in vivo [28]. However, B[a]P-induced genotoxicity is mainly caused by damage from BPDE-DNA adducts as well as ROS-based DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin, a natural flavonoid, is a constituent of milk thistle (Silybum marianum). It is a metabolic regulator known to have anti-oxidant, anti-inflammatory, anti-cancer, anti-mutagenic, anti-bacterial, and anti-virus effects [27][28][29][30]. Furthermore, silymarin has multiple pharmacological activities and its components include silibinin, silydianine, and silychristin [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary function of phase I metabolism is the ease of drug absorption and its effect on compound preparation for phase II metabolism. Phase II metabolism is detrimental to xenobiotics and drug detoxification in obtaining water-soluble products (Kiruthiga et al, 2015). In vivo studies, cyt.b 5 and cyt.b 5 R increased levels of all measured components.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that the presence of CYP1A1 activated the BaP and subsequently resulted in the initiation of the said tumours. The flavonoid, silymarin was shown to block the activation of BaP in Wistar rats via the inhibition of CYP1A1 and so it is deemed to possess chemopreventive properties (Kiruthiga et al, 2013).…”
Section: Phytochemicalsmentioning
confidence: 99%